Richard Ford and the Ends of Realism - McGuire, Ian (Book collections on Project MUSE., 2015)
"An original exploration of the work of writer Richard Ford in the context of its place within contemporary debates about the possible role, meaning of, and value of literary realism in a postmodern age"--